Law Enforcement Against Hate Speech Perpetrators on Social Media in Legal History and Criminal Law Reform - Simaremare, Simon; Sudjiarto, Tatok; Panggabean, Mompang L (Judge : Jurnal Hukum, 2024)
The aim of this writing is to map out appropriate punishments for the actions of perpetrators involved in hate speech on social media. Every act of hate speech needs to be given the correct article and not equate it with the perpetrator's actions through various media to carry out hate speech. The research method used is Normative legal research methods are assisted by secondary data such as theories, ideas, standards and court decisions about how important it is to change criminal law regarding hate speech on social media to achieve the desired goals. The results of the research show that there is a need for political restoration of criminal law and legal reform in the interpretation of each article and paragraph, so that it is prepared based on the case and not mixed up in giving punishment. The law is good, the people are good. On the other hand, the law is a mess, so the people are also a mess.